Обґрунтування періодичності технічного обслуговування агрегатів очищення мастила в двигунах внутрішнього згоряння - Дашивець, Галина Іванівна; Дашивец, Галина Ивановна; Dashyvets, Halyna; Новик, Олексій Юлійович; Новик, Алексей Юльевич; Novik, Oleksii; Паніна, Валерія Валеріївна; Панина, Валерия Валерьевна; Panina, Valeriia (My University, 2019)
UK: Роботу присвячено дослідженню різних систем очищення мастила в двигунах Д-240: серійна схема; серійна схема, де центрифуга має захисну сітку; комбінована система: серійна центрифуга на повному потоці і паперовий фільтр на відгалуженні. Спостереження велось за двигунами протягом періоду накопичення відкладень агрегатами очищення до повної брудовміскості. Зміна якості мастила проводилось по фізико-хімічним показникам: лужному числу, вмісту механічних домішок, продуктів зносу, кінематичній в'язкості, часу накопичення агрегатами повної грязеємності та щільності осаду. Отримані дані показали, що більші значення терміну напрацювання двигуна до моменту повної брудовміскості, щільності осаду і маси були при експлуатації комбінованої системи очищення, що дозволило використовувати мастило і обслуговувати агрегати очищення з періодичністю, що дорівнює міжсезонному технічному обслуговуванню. RU: работа посвящена исследованию различных систем очистки масла в двигателях Д-240: серийная схема; серийная схема, где центрифуга имеет защитную сетку; комбинированная система: серийная центрифуга на полном потоке и бумажный фильтр на ответвлении. Наблюдения велись за двигателями на протяжении периода накопления отложений агрегатами очистки до полной грязеёмкости. Изменение качества масла проводилось по физико-химическим показателям: щелочному числу, содержанию механических примесей, продуктов износа, кинематической вязкости, времени накопления агрегатами полной грязеёмкостии плотности осадка. Полученные данные показали, что большие значения срока наработки двигателя до момента полной грязеёмкости, плотности осадка и массы были при использовании комбинированной системы очистки, что позволило использовать масло и обслуживать агрегаты очистки с периодичностью, равной межсезонному техническому обслуживанию. EN: The work is devoted to the study of various systems for cleaning lubricants in engines D-240: serial scheme; centrifuge serial scheme having a protective grid; Combined system: full flow batch centrifuge and paper filter on the branch. It is proved that the deterioration of the physical and chemical parameters of the lubricant during the operation of the engines corresponds to the accumulation of deposits in the rotors of centrifuges. The observation was carried out by the engines D-240 during the period of accumulation of deposits by cleaning units to full dirt. Lubrication samples were selected after a certain period of operation of the engine to detect the dynamics of oil change. At the same time, the control of filling the centrifuge rotors with polluting impurities was carried out by partial disassembly and weighing of the glass after draining of the lubricant from the internal surface of the precipitate. The quality of the lubricant was evaluated according to the physic-chemical parameters: alkaline number, content of mechanical impurities, products of wear, kinematic viscosity, accumulation time of aggregates of full mud capacity and sediment density. Studies have shown that the use of a combined purification system leads to stabilization of the alkaline additive treatment process, which occurs earlier and at a higher level. The content of mechanical impurities and deterioration products using this scheme of purification system is at a lower level compared to serial centrifuges. Summary of article. Larger values of the engine lifetime until the moment of full dirt holding capacity, sediment density and mass, which were during the operation of the combined purification system, will allow the use of lubricant and serve cleaning units with a periodicity equal to inter-season maintenance.
Обоснование периодичности технического обслуживания агрегатов очистки масла в двигателях внутреннего сгорания
Justification of the periodicity of the technical service of oil cleaning units in internal combustion engines
Keywords: моторне мастило; система очищення; центрифуга; фізико-хімічні показники; лужне число; вміст механічних домішок; продукти зносу; кінематична в'язкість; моторное масло; система очистки; центрифуга; физико-химические показатели; щелочное число; содержание механических примесей; продукты износа; кинематическая вязкость; motor oil; purification system; centrifuge; physical and chemical parameters; alkaline number; content of mechanical impurities; attrition products; kinematic viscosity